PENGARUH PERTUMBUHAN ASSET TERHADAP KINERJA KEUANGAN PT. PELABUHAN INDONESIA IV (PERSERO) CABANG MAKASSAR - Arifani (FEB Universitas Lakidende, 2020)
This study aims to analyze the Effect of Asset Growth on the Financial Performance of PT. Pelabuhan Indonesia IV (Persero) Makassar Branch. Analysis of the data used in this research is Descriptive Analysis using time span data of 5 years from 2014 to 2018. The results of this study indicate that Asset Growth has a positive and significant effect on the financial performance of PT. Pelabuhan Indonesia IV (Persero) Makassar Branch.